NILAI PENGANTIN PEREMPUAN DALAM MAS KAWIN SUKU BANGGAI DITINJAU DARI KONSEP IMAGO DEI DALAM KEJADIAN 1:26-27 - Yusdian Lumbon; Ermin Alperiana Mosooli; Oskar Sopang (SEKOLAH TINGGI TEOLOGI KIBAID, 2021)
This study aims to examine the bride's value in the Banggainese (in Central Sulawesi Province, Indonesia) dowry tradition from the concept of man and woman as Imago Dei in Genesis 1: 26-27. The method used is a literature study with content analysis as a data analysis technique. The results showed that the prospective bride's value in the Banggainese dowry tradition contradicts the human concept as Imago Dei in Gen 1: 26-27. As Imago Dei, women and men are created equal and are equally servants of Allah whose position is above other creations. The bride's value in the Banggainese dowry tradition shows that women's status is lower than men. It put a prospective bride as an object who could exchange for family prestige and adjusted with things like money.